(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Background: Childhood begins after birth and continues into adolescence; according to the Children’s Bill of Rights, childhood is defined as the life up to 18 years after birth. Childhood mortality is a reliable indicator of health care facilities of a country and its development. Aims & Objective: Assessment of medico–legal profile among the unnatural deaths in paediatric age group at SMS Hospital, Jaipur Material & Methodology: A cross sectional observational prospective study that used inclusion and exclusion criteria was conducted. 65 autopsies of medico-legal paediatric unnatural death were taken in the study. The present study had been conducted in the Mortuary, Department of Forensic Medicine & Toxicology, SMS Hospital, Jaipur during the period from 15 June 2021 to 14 June 2022. Result & Observation: In this study total 65 pediatric victims studied. Male children account for 61.54 % (40 victims) while female account for 38.46 % (25 victims), unintentional pattern of death was present in 49 subject with accidental manner of death in all. Intentional pattern of death was present in 16 subject with homicidal manner of death in 6.15 % and suicidal manner of death in 18.45 %, In present study 23 subject (35.38 %) died due to Road Traffic Accident, followed by Fall From Height in 12 subject (18.45 %). Conclusion: From the study we concluded that there is an immense responsibility for the parents and caregivers in supervising their children. If the incident cannot be prevented, the victim should receive immediate care right away in order to save their life.